A New Species of Osedax (Siboglinidae: Annelida) From Colonization Experiments in the Arctic Deep Sea - Eilertsen, Mari Heggernes; Dahlgren, Thomas G.; Rapp, Hans Tore (Frontiers in Marine Science, 2020)
Large parcels of organic matter in the deep sea, such as whale carcasses, harbor a very specialized fauna, most famously the bone-eating worms in the genus Osedax (Annelida, Siboglinidae). Although Osedax was first described only 15 years ago, there are already 26 described species from the Pacific, Atlantic and Southern Oceans. The high discovery rate of new Osedax species indicates that there is still a lot of undescribed diversity. In this study we describe the most northerly species of Osedax to date, Osedax fenrisi sp. nov. from 73°N on the Arctic Mid-Ocean Ridge. We also present an updated molecular phylogeny of Osedax based on COI and 18S, including all described species in the genus. The molecular results support that Osedax fenrisi sp. nov. is distinct from the previously known species of Osedax. Both morphological characters and the molecular phylogeny support the placement of Osedax fenrisi sp. nov. in clade V. The most striking morphological character shared with other described species in this clade (O. rubiplumus, O. roseus and O. bryani) is the presence of long pinnules inserted on the outside of the palps.